The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/acs.2014.42028
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Air Pollution in Kuwait City Using Passive Samplers

Abstract: Measurements of gaseous SO 2 , NO, NO 2 , H 2 S, O 3 , NH 3 and VOCs, in Kuwait city using IVL passive sampler technology, were obtained on monthly basis during the period from March 2011 to February 2012 at 10 locations. The results of this study reveal that those compounds had low concentrations compared to Kuwait Environment Public Authority standards for residential areas. It is found that nitrogen oxides, benzene and xylene were mostly emitted from motor vehicles; in contrast, industrial sources including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Background concentration checks using zero air were conducted to correct instrument drift. Highpurity air was sent into the instruments to obtain a daily true zero [Al-Awadhi, 2014].…”
Section: Air Pollution Samplingmentioning
confidence: 99%
“…Background concentration checks using zero air were conducted to correct instrument drift. Highpurity air was sent into the instruments to obtain a daily true zero [Al-Awadhi, 2014].…”
Section: Air Pollution Samplingmentioning
confidence: 99%
“…They, therefore, concluded that these monitoring stations should be relocated to increase the efficiency of the KU-EPA monitoring network. Al-Awadhi, [21] used passive sampler technology to measure many air pollutants gases in Kuwait city on the monthly basis. He reported that gas pollutants had low concentrations compared to KU-EPA standards for residential areas.…”
Section: Introductionmentioning
confidence: 99%
“…Kuwait is by no means an exception in the above situation (Al-Awadhi, 2014). There are substantial challenges of environmental concerns in the country due to human life activities.…”
Section: Introductionmentioning
confidence: 99%
“…Actually consequences of this act are still unfolding. Added to this is the pollution contributed by urban and industrial activities such as vehicle trafficking and industrial plants among many (Al-Awadhi, 2014), which are expanding as Kuwait population and its demands increases. As mentioned before the impacts inflicted on the ecosystem by human's activities are hard to track let alone identify their consequences short and long.…”
Section: Introductionmentioning
confidence: 99%